2018
DOI: 10.1007/s11306-018-1447-4
|View full text |Cite
|
Sign up to set email alerts
|

The altered human serum metabolome induced by a marathon

Abstract: and Loots, Du Toit (2018) The altered human serum metabolome induced by a marathon. Metabolomics, 14 (11). p. 150.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 65 publications
7
57
1
Order By: Relevance
“…Carbohydrates, glucose in particular, are considered to be the primary fuel substrates used by the body during physical activity. Stander et al 10 and Lewis et al 6 reported severely elevated serum concentrations of various carbohydrates immediately after a marathon (day 0). In this metabolomics investigation, it is clear that the majority of the serum carbohydrates (glucose and mannose) and associated metabolites (uridine, ribose, glycerol, and myo-inositol) returned to baseline (pre-marathon) concentrations within 24 h post-marathon (Table 1), with the exception of xylose (also dietary-related).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrates, glucose in particular, are considered to be the primary fuel substrates used by the body during physical activity. Stander et al 10 and Lewis et al 6 reported severely elevated serum concentrations of various carbohydrates immediately after a marathon (day 0). In this metabolomics investigation, it is clear that the majority of the serum carbohydrates (glucose and mannose) and associated metabolites (uridine, ribose, glycerol, and myo-inositol) returned to baseline (pre-marathon) concentrations within 24 h post-marathon (Table 1), with the exception of xylose (also dietary-related).…”
Section: Resultsmentioning
confidence: 99%
“…www.nature.com/scientificreports/ www.nature.com/scientificreports/ Table 1 depicts the recovery trend of the metabolites not only initially affected by the marathon perturbation, but also the concentration fluctuations of additional metabolites pertinent to the 24 h and 48 h recovery period. In order to ascertain the metabolic recovery mechanisms following a marathon, it is imperative to first consider the immediate effects of a marathon on the serum metabolome of athletes, which was characterised and previously described by Stander et al 10 . Briefly, alterations were mainly observed in metabolic pathways associated with energy production, such as elevated concentrations of various carbohydrates, TCA cycle intermediates, fatty acids and ketone bodies, and reduced concentrations of various amino acids and associated metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…One of the mechanisms of insulin resistance is inflammation-induced upregulation of tryptophan metabolism in combination with P-5-P-deficiency-induced diversion of tryptophan metabolism leading to formation of xanthurenic acid and other kynurenine derivatives that affect insulin activity (Oxenkrug, 2013). It has been shown that reduced insulin levels may lead to uncontrolled glucose metabolism -previously described in individuals with diabetes (American Diabetes Association, 2013), pulmonary TB (Preez et al, 2017) and, recently, in runners after a marathon (Stander et al, 2018), all of which are associated with a severe inflammatory response. As depicted in our model, uncontrolled glucose metabolism can result in glucose being oxidized via glucose oxidase to produce gluconolactone, in addition to hydrogen peroxide, previously reported to occur in both diabetes and pulmonary TB (Preez et al, 2017).…”
Section: Proposed Predictive Metabolic Model Of Tbm In the Brain Basementioning
confidence: 99%
“…During prolonged and intensive running, lipolysis, proteolysis, glycogen depletion, and hepatic gluconeogenesis are enhanced in marathon runners to supply the body with sufficient energy [10]. More precisely, β-oxidation and the tricarboxylic acid cycle (TCA) are activated to deliver substrates for ATP production [12]. At lower exercise intensities (50%-60% VO 2 max), fat and carbohydrate oxidation both contribute to ATP generation.…”
Section: Acylcarnitinesmentioning
confidence: 99%
“…In one of the earliest studies, Lewis et al used a targeted metabolomics approach to analyze 25 runners who participated in the Boston Marathon [10]. They observed a reduction in glucogenic amino acids and an increase of metabolites related to lipolysis and ketone body production, and these findings have been confirmed in more recent studies using improved MS technology [6][7][8]11,12]. Post-race concentrations of plasma glycerol were highest among runners with a higher relative maximum oxygen uptake (VO 2 max) compared to those with lower aerobic capacities.…”
Section: Introductionmentioning
confidence: 96%